The new school of convict criminology thrives and matures - Richards, Stephen C. (Critical criminology, 2013)
This article discusses the past, present, and future of the New School of Convict Criminology (CC). A short history, including a discussion of literature, major works, and research studies is provided as is a review of Convict Criminology Group origination, membership, and activities. A first attempt at formal Convict Criminology Theory construction is presented alongside four research hypotheses. University prejudice and exclusion, as well as criminal justice hate words, are also addressed. The conclusion explores the future of CC and requests support for the movement.